Gut microbiota composition is associated with disease severity and host immune responses in COVID-19 - Fan, Ruyue; Liu, Shuai; Sun, Na; Yang, Ying; Deng, Xia; Hu, Bin; Sun, Changhua; Wen, Chengli; Li, Hui; Cheng, Dong; Huang, Chuanjun; Hou, Peibin; et al. (Frontiers in Cellular and Infection Microbiology, 2023)
Background Human gut microbiota play a crucial role in the immune response of the host to respiratory viral infection. However, evidence regarding the association between the gut microbiome, host immune responses, and disease severity in coronavirus disease 2019 (COVID-19) remains insufficient. Methods To better comprehend the interactions between the host and gut microbiota in COVID-19, we conducted 16S rRNA sequencing and characterized the gut microbiome compositions in stool samples from 40 COVID-19 patients and 33 non-pneumonia controls. We assessed several hematological parameters to determine the immune status. Results We found that the gut microbial composition was significantly changed in COVID-19 patients, which was characterized by increased opportunistic pathogens and decreased commensal bacteria. The frequency of prevalent opportunistic pathogens Enterococcus and Lactobacillus increased, especially in severe patients; yet the abundance of butyrate-producing bacteria, Faecalibacterium, Roseburia, and Anaerostipes, decreased significantly, and Faecalibacterium prausnitzii might help discriminate severe patients from moderate patients and non-pneumonia people. Furthermore, we then obtained a correlation map between the clinical characteristics of COVID-19 and severity-related gut microbiota. We observed a notable correlation between the abundance of Enterococcus faecium and abnormal neutrophil or lymphocyte percentage in all COVID-19 patients. Faecalibacterium was positively correlated with lymphocyte counts, while negatively correlated with neutrophil percentage. Conclusion These results suggested that the gut microbiome could have a potential function in regulating host immune responses and impacting the severity or consequences of diseases.